Optimalisasi Pojok Baca Melalui Gerakan Literasi Dasar di SD Negeri 2 Raja Ampat - Greisela Togelang; Desti Rahayu; Asrul Asrul (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This research was motivated by the phenomenon of very low reading and writing skills in class II D students. This research aims to describe the implementation of reading and writing literacy through the reading corner in class II D SD N 2 Raja Ampat, and describe the inhibiting and supporting factors in the implementation of reading and writing literacy through the reading corner in class II D SD N 2 Raja Ampat. This research also uses a qualitative method,case study research design. Data collection techniques in this research used observation,interviews and documentation.the data analysis technique uses data reduction, presenting data and drawing conclusions. The results of this research show that the implementation of reading and writing literacy through the reading corner in class II D SD SD N 2 Raja Ampat,(1) before learning begins the teacher teaches reading and writing for 15 minutes; (2) during Indonesian language learning the teacher directs student read any story book according to the student’s wishes then the teacher asks student to retell what they read in front of their friends; (3) during break time, after students have finished eating, and in the remaining time students are asked to read and write through reading corner until break time is over; (4) fill free time with reading and writing literacy; (5) reading and writing literacy 15 minutes before going home from school. Researchers found 4 inhibiting factors, (1) students who cannot read and write; (2) we still use old books; (3) ack of support from some parents in reading and writing literacy; (4) students do not know letters and letter shapes A-Z. And 4 supporting factors (1) encouragement from the head of the school; (2) support from some of the student’s parents (3) supported by facilities and infrastructure which, althrough not very adequate (4) students have implemented reading and writing literacy in the reading corner, when literacy time has arrived without being directed by the teacher. Because the students have their own desires.